Foreign Exchange Markets - Coyle, Brian (Chicago: Glenlake Pub. Co., 2000)
This book describes the buying, selling, depositing, borrowing, and lending of foreign currency. It begins by explaining how the foreign exchange markets are structured and proceeds to examine spot transactions and forward exchange contracts. Finally it explains swaps transactions and short-dated forward transaction.
Includes index.
lje 09/0913
Loans
Keywords: Money market; International finance; Foreign exchange market